Dynamics of the absorption of forms of N by crops plants - Retheesh PK (Department of Agronomy, College of Horticulture, 1995)
An investigation was conducted at the Radiotracer Laboratory, College of Horticulture, Vellanikkara in the year, 1993 which consisted of two parts. In the first part absorption of different forms of nitrogen relative to its concentrations at different growth stages of rice was studied using labelled and non-labelled fertilizers. To know the molecular absorption of urea 14C-labelled urea fertilizer was used and the presence of 14C in the plant was taken as an evidence for the absorption of molecular form of urea. In the case of ammoniacal and nitrate forms of N, 15N-labelled and non-labelled materials were used alternately to find out the preferential absorption. In the second part of the investigation an attempt was made to know the possibility of molecular absorption of urea by a few selected plantation crops. The uptake of N and dry matter production were higher when rice plants were supplied with a combination of ammonium and nitrate in equal proportions. Among the three forms of nitrogen supplied at different combinations, nitrate N recorded the highest uptake when present along with urea N or ammoniacal N or both. Though the presence of urea had a repressing effect on the uptake of nitrate, ammonium enhanced the nitrate uptake. The uptake of nitrate N was more in the presence of ammonium than in its absence. With respect to ammonium uptake it was found that urea and nitrate had more or less similar influence on it. It was seen that rice plants absorbed molecular form of urea even in the presence of other readily available forms of nitrogen. The molecular absorption of urea by rice plants was found to vary from 12-18 percentage of the total N uptake. When urea was supplied along with ammonium and or nitrate the uptake of urea was found reduced. The quantity of urea absorbed by the plantation crops was found negligible and ranged from 0.5-3.3 µg per g of the plant dry weight.